Global inequality in length of life: 1950-2015 - Vanesa Jordá; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper provides a broad picture of national, regional and global trends of inequality in length of life over the period 1950-2015. We use data on life tables from World Population Prospects to develop a comprehensive database of a battery of inequality measures for 201 countries at five-year intervals over the period under analysis. We estimate both absolute and relative inequality measures which have the property of being additively decomposable. This property makes the database remarkably flexible because overall inequality can be computed for any group of countries using only the information included in our database. The decomposition analysis reveals that differences in life expectancy between countries account for a very small portion of the observed changes in global inequality in length of life, evolution of which is large driven by within-country variation. Our estimates indicate that inequality in length of life has decreased sharply since 1950, a reduction that can be largely attributed to the substantial progress made in reducing child mortality worldwide. We also observe a degree of heterogeneity in the distributional patters of inequality in length of life across world regions.
Keywords: D63; I01; I14; 330; inequality; lifespan; mortality rates; life expectancy